Simulations of Routing Protocols for Inbound/Outbound Traffic Based on Opnet'm - Vasudha,; Sharma, Ajay K; Kumar, Manoj (Gyan Management Journal, 2010)
Routing is a relevant issue for maintaining good performance and successfully operating in a network. In computer networks, routing protocols are triggered to update routing and forwarding tables. Because of invalid tables during update-time, transient loop may occur and packet-drop rate and end-to-end delay increase which means that the quality of service decreases. In any IP network, routing protocols provide the intelligence that takes a collection of physical links and transforms them into a network that enables packets to travel from one host to another. In this paper the performance evaluation for the combination of conventional model of"RIP" and "EIGRP" routing protocols for inbound and outbound traffic has been presented
Keywords: Routing Protocol; Inbound/outbound Traffic; RIP and El GRP